Asean Paradox: Between Asean's Commitment to Migrant Worker Protection and the Protection of Indonesian Migrant Workers - Yogo Pamungkas; Anda Setiawati; Andari Yurikosari; Mohamad Fauzan (Green Publisher Indonesia, 2025)
ASEAN has created various instruments to protect migrant workers, such as the ASEAN Declaration on the Protection and Promotion of the Rights of Migrant Workers (2007) and the ASEAN Consensus on the Protection and Promotion of the Rights of Migrant Workers (2017). However, despite these regional commitments, Indonesian migrant workers (PMI) continue to face exploitation, discrimination, and inadequate legal protection. This study aims to evaluate the effectiveness of ASEAN instruments in protecting migrant workers by analyzing the gaps between regional policies, national regulations, and bilateral agreements. Using a qualitative approach with document analysis, this research examines ASEAN instruments, Indonesian regulations, and bilateral agreements to identify implementation challenges, problems, and possibilities. The results show that ASEAN's ineffectiveness stems from the inadequate binding force of the instruments, lack of enforcement mechanisms, weak coordination among member states, and minimal participation of migrant workers in the policy process. These findings demonstrate significant disparities between stated commitments and actual protection outcomes for Indonesian migrant workers. This research makes theoretical contributions by enriching the literature on regional governance and practical implications by offering policy recommendations to strengthen the protection of migrant workers in the ASEAN region.